Shifting mechanisms of elevational diversity and biomass patterns in soil invertebrates at treeline. (October 2017) - Xu, Guorui; Lin, Yinghua; Zhang, Shuang; Zhang, Yuxin; Li, Guixiang; Ma, Keming
Abstract: Ecologists and biogeographers have long been interested in the underlying mechanisms shaping the elevational patterns of biodiversity. However, most of these studies have been conducted aboveground. Although they deliver key ecosystem functions and services, the elevational diversity and biomass patterns of soil invertebrates, including a wide range of taxa, have been severely understudied, especially at treeline. To address this critical gap, we identified richness, abundance, and biomass patterns of soil invertebrates across an elevational gradient under below-treeline forest (from 1020 to 1770 asl) and above-treeline meadow (from 1790 to 2280 asl), respectively. We aimed to (1) identify the elevational patterns of richness, abundance, and biomass in soil invertebrates across the treeline; and (2) test whether these patterns break and the underlying mechanisms shift at the treeline. We found that both the diversity and biomass of litter-dwelling invertebrates showed hump-shaped patterns below the treeline and monotonically decreasing patterns above the treeline, respectively. Richness association of litter-dwelling invertebrates and herbaceous plants shifted from negative to positive at the treeline. For the soil-dwelling invertebrates, no elevational trends were detected in forest while the diversity decreased monotonically with elevation in meadow. In contrast to basal area and litter thickness in forest, temperature was most strongly related to the diversity of litter-dwelling invertebrates in meadow. We showed the breaks in elevational diversity patterns of soil invertebrates at the treeline, while elevational patterns of biomass did not change. Microclimate replaced productivity as the most important factor driving the diversity patterns of litter-dwelling invertebrates across the treeline with vegetation shifts induced by increasing elevation. Highlights: Elevational richness, abundance and biomass patterns were concurrent examined. Elevational diversity patterns of soil invertebrates broke at treeline. Contrasting richness association of soil invertebrates and plants across treeline. Microclimate replaced productivity driving elevational diversity pattern above treeline.